Changes in Seed Yield and Mucilage of Fenugreek (Trigonella foenum-graecum L.) in Response to Foliar Application of Methanol as a Bio-stimulant - A Mehrafarin; H Naghdi Badi; A Qaderi; MR Labbafi; E Zand; Gh Noormohammadi; N Qavami; M Seif Sahandi (Institue of Medicinal Plants, ACECR, 2015)
Background: Fenugreek is a multipurpose and valuable medicinal plant that its consumption of seeds in the pharmaceutical industry for the economically production of mucilage (galactomannan) and trigonelline is very important. Foliar application of methanol as a biostimulant on C3 plants such as the fenugreek can increase the CO2 fixation in photosynthesis and decrease photo-respiration and the result will produce more dry matter in these plants. Objective: The aim was to determine changes in seed and mucilage yield of fenugreek in response to foliar application of different concentrations of methanol. Methods: This research was carried out at the experimental farm of Medicinal Plants Institute (MPI) of Academic Center for Education, Culture & Research (ACECR) located in Karaj during two cropping seasons based on a randomized complete block design with 5 treatments and 3 replications. Foliar application during the growing season was run 3 times with 12 days interval. The treatments were control (sprayed with distilled water without methanol) and foliar application of four different concentrations of methanol (10, 20, 30 and 40 volumetric percent). Results: Foliar application of different concentrations of methanol had a significant effect on number of branches per plant, number of leaves per plant, shoot dry weight, number of pods per plant, number of seeds per pod, seed yield, yield of seed mucilage, seed ash content, seed swelling index (p≤0.01), plant height, and 1000 seeds weight (p≤0.05). Conclusion: Foliar application of methanol as a bio-stimulant and the new method in production of medicinal plants improved seed yield and yield of seed mucilage in fenugreek. In general, the maximum amounts of the studied traits were achieved in the foliar application of 40% v/v methanol concentration.